Gay men and intimate partner violence: a gender analysis. Issue 4 (19th March 2014) - Oliffe, John L.; Han, Christina; Maria, Estephanie Sta.; Lohan, Maria; Howard, Terry; Stewart, Donna E.; MacMillan, Harriet
Abstract Though intimate partner violence (IPV) is predominately understood as a women's health issue most often emerging within heterosexual relationships, there is increasing recognition of the existence of male victims of IPV. In this qualitative study we explored connections between masculinities and IPV among gay men. The findings show how recognising IPV was based on an array of participant experiences, including the emotional, physical and sexual abuse inflicted by their partner, which in turn led to three processes. Normalising and concealing violence referred to the participants' complicity in accepting violence as part of their relationship and their reluctance to disclose that they were victims of IPV. Realising a way out included the participants' understandings that the triggers for, and patterns of, IPV would best be quelled by leaving the relationship. Nurturing recovery detailed the strategies employed by participants to mend and sustain their wellbeing in the aftermath of leaving an abusive relationship. In terms of masculinities and men's health research, the findings reveal the limits of idealising hegemonic masculinities and gender relations as heterosexual, while highlighting a plurality of gay masculinities and the need for IPV support services that bridge the divide between male and female as well as between homosexual and heterosexual.